2008
DOI: 10.1143/apex.1.032003
|View full text |Cite
|
Sign up to set email alerts
|

Second Harmonic Generation with High Conversion Efficiency and Wide Temperature Tolerance by Multi-Pass Scheme

Abstract: We proposed a multi-pass second harmonic generation scheme in which condensed fundamental light passed through a nonlinear crystal many times. The multi-pass scheme was realized by using a wide periodically-poled MgO:LiNbO3, concave mirrors and condensing optics. The total wavelength conversion efficiency of the multi-pass scheme was increased because non-converted fundamental light which had passed through the nonlinear crystal was re-injected and condensed into the nonlinear crystal and converted. Moreover t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…At low to moderate fundamental powers (<10 Watts), where cw SP-SHG efficiency is hampered by low nonlinear gain, the use of the longest crystal length is imperative to obtain practical output power. To enhance efficiency and power, schemes such as double-pass and multi-pass pumping may be deployed [24,25] to increase the effective interaction length. However, successful exploitation of such techniques requires accurate control of relative phase in successive passes through the crystal to compensate for phase-mismatch, using dispersion in air [26,27] or wedged crystals [28].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At low to moderate fundamental powers (<10 Watts), where cw SP-SHG efficiency is hampered by low nonlinear gain, the use of the longest crystal length is imperative to obtain practical output power. To enhance efficiency and power, schemes such as double-pass and multi-pass pumping may be deployed [24,25] to increase the effective interaction length. However, successful exploitation of such techniques requires accurate control of relative phase in successive passes through the crystal to compensate for phase-mismatch, using dispersion in air [26,27] or wedged crystals [28].…”
mentioning
confidence: 99%
“…The use of double-pass or multi-pass pumping is also not as desirable at high pump powers as may be entertained at low powers, because of the increased risk of damage and thermal effects. To minimize such risks, multiple single-pass pumping in a 25-mm-long, wide-aperture MgO:PPLN crystal has been used, resulting in a cw SHG efficiency of 66% [25], but the resulting poor quality of the output beam limits the effectiveness of this approach. As such, enhancement of cw SHG conversion efficiency by deploying multi-pass configurations requires careful optimization and proper engineering of the nonlinear crystal [24].…”
mentioning
confidence: 99%
“…In these cases the crystal is either positioned inside a resonator or multiple passes in one or consecutive crystals are used to increase the effective length of the nonlinear material. All concepts are increasingly complex but lead to higher conversion efficiencies [105,[173][174][175].…”
Section: Concepts For Nonlinear Frequency Conversionmentioning
confidence: 99%
“…Lai et al [14] reported 30% and 7.5 W in the same configuration. A higher conversion efficiency of 66% was demonstrated by Mizushima et al, who reported an output power of 5 W using a multi-pass scheme instead [15]. These three reports all used a crystal length of 25 mm and CW excitation.…”
Section: Introductionmentioning
confidence: 96%